THE INTERNET OF THINGS TECHNOLOGIES FOR MONITORING THE PHYSICAL LOADS OF CYCLISTS - zhuravska, iryna; Пилипчук, Богдан (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work reveals the principles of using the Internet of Things technology (IoT) in modern sports with an emphasis on the organization of training regimes and competitions in cycling sport. This technology is a reliable way of collecting data, but it involves the selection of certain scales for evaluating the physical loads of athletes and the correction of the coach in adjusting the training regimes selected with the help of the cyber-physical system. The most common among athletes are the FTP scale and the VAMs scale. The most suitable for combining the features of the application of IoT technology and the selected scales are sensors built into sports gadgets manufactured by Garmin – watches, fitness bracelets, GPS devices, etc., which record various data during cyclist activity. This data have stored by the Garmin Connect web application and can been classificated as Big Data. Access to the necessary information can be obtained by exporting a data file in *.csv format from the site. The architecture of the software includes a client application and a layer of working with data, implemented in the Python programming language using appropriate libraries. The software is aimed at processing and visualizing statistical data to facilitate the assessment of physical fitness and training adjustments of cyclists. The proposed solution takes into account that IoT technologies should provide for the connection of various specialized modules and sensors, including those of our own development, and not only Garmin sensors populared among cyclists. Therefore, the basis of the developed software are such possibilities as scalability and flexibility, which will in the future ensure the exchange of data between the embedded sensors into cyclists' equipment and the computer system in automatic mode using standard communication protocols in accordance with the concept of IoT.
Keywords: Internet of Things; cyber-physical system; sensors; cycling sport; physical loads monitoring; information system; Big Data